PROPHETIC PSYCHOLOGY: ACADEMIC IMPRESSIONS OF AN AFRICAN CONVERT/REVERT TO ISLAM - Shikongo, Armas EE (International Prophetic Conference (SWAN) FPQS USIM, 2022)
Prophetic Psychology, otherwise popularly known amongst Muslims as Hikmah or Strategic Wisdom in the English language, refers to a form of a high cognitive state characterized by higher moral values, ethics and principles that ideologically guide to what is universally and culturally good for all humans, times and ages. This paper focuses on the concept of Prophetic Psychology as a way to focus on the noble lessons that can be derived from the Prophetic Model in terms of the best practices for human relations and personal development. The paper contains academic impressions of an African convert/revert to Islam in relation to Prophetic Psychology, specifically from Southern Africa, Namibia.